Ambivalensi Ketakutan dalam Film Incantation, The Medium, dan Keramat: Kajian Penyimpangan Kenikmatan dan Korelasi Pada Abjek Profan - Chintya Angesty; Muhammad Hamdan Mukafi (Balai Bahasa Sulawesi Selatan, 2024)
Fear is a human mental experience often enjoyed as a release of adrenaline. People do not avoid horrors initially objectified as profane. Although this view persists, they are often unaware that they derive pleasure from what is considered “abnormal.” This study aims to explore the power of narrative in folk horror films, which plays a pivotal role in enabling audiences to derive aberrant pleasure from fear. Using a qualitative descriptive method, the research applies Julia Kristeva’s The Power of Horror and Adam Scovell’s folk horror theory. The formal object of analysis is abjection, while the material objects are three Asian folk horror films: Incantation (2022), The Medium (2021), and Keramat (2009). The findings reveal that these films allow viewers to experience horror and cruelty as something awe-inspiring. The admiration for fear, evoked by recollections of folk narratives, leaves a profound impression, making folk horror a medium that satisfies the human desire for superiority in mastering cruelty and fear. This study contributes to understanding Asian folk horror films, which are currently thriving in production due to their broad market appeal, rooted in Asia's rich mysticism.